Evaluation of E-Government Governance with the Implementation of the COBIT 2019 Method at the West Pasaman Civil Registration Office - Septiawan, Edo; Veri, Jhon; Sumijan, S (Jurnal KomtekInfo, 2025)
The rapid development of information technology has encouraged government agencies to adopt Electronic Government (E-Government) to improve the efficiency, transparency, and accountability of public services. However, implementation challenges remain, especially in regional agencies such as the Population and Civil Registration Office (Dukcapil) of West Pasaman Regency, where inconsistencies and lack of system integration are still widespread. This study aims to analyze and evaluate E-Government governance. The method used in this study is the COBIT 2019 framework to assess the level of capability and propose strategic improvements in IT service management. This study adopted a qualitative case study approach, guided by the COBIT 2019 Design and Implementation framework. Data were collected through direct observation and in-depth interviews with Dukcapil personnel, supported by 145 structured questions and documentary analysis. This process focuses on five COBIT processes: EDM04 (Ensure Resource Optimization), APO07 (Manage Human Resources), BAI09 (Manage Assets), DSS01 (Manage Operations), and MEA01 (Monitor, Evaluate, and Assess Performance and Conformance). The results show that the capability level of the DSS01 process is at level 2 (Managed Process), while the capability target is level 3 (Established Process). This gap reflects the need for improvement in operational process management, including strengthening documentation and standardizing practices. Based on these results, strategic recommendations are developed that are contextually oriented to local bureaucratic conditions. This research can be a reference for the implementation of COBIT 2019 to effectively identify governance weaknesses and provide actionable strategies in increasing E-Government maturity at the regional level, supporting better service delivery and organizational performance.